Correlation of Morphological Traits with Milk Production in Murrah Buffaloes - , Subhasish Sahu; , Anjali Arya; , Dipankar Kar; , Archana Sarangi (Archives of Current Research International, 2024)
The current investigation aimed to assess the correlation between morphometric characteristics and production performance in Murrah buffaloes, recognized as the premier milch breed globally. A cohort of 100 lactating Murrah buffaloes in their first to third lactation cycles was selected from the Buffalo Farm at Lala Lajpat Rai University of Veterinary and Animal Science, Hisar. The study focused on five traits: 305 days of lactation yield, muzzle width, brisket width, hip width, and skin thinness. Statistical analysis was conducted using Pearson's correlation method. The findings revealed negative correlations between lactation yield and the morphometric traits of muzzle width, brisket width, and hip width. Conversely, a positive correlation was observed between lactation yield and skin thinness. This study provides valuable insights for selecting dairy Murrah buffaloes that exhibit optimal production under field conditions, as these identified traits can be considered pivotal factors in the decision-making process for buffalo selection in dairy production systems.